The efficiency of artificial intelligence in reducing financial losses caused by disasters - Ščetić, Samir; Tatarević - Ščetić, Lejla; Salkić, Hadžib (Crisis Management Days, 2024)
Artificial intelligence (hereinafter AI) is increasingly becoming a key tool in reducing financial losses caused by disasters. Through the application of advanced machine learning algorithms, AI enables rapid recognition and analysis of disaster-related data, facilitating the prediction of their financial consequences. AI systems can analyze vast amounts of data such as meteorological, seismic, and social information to create precise risk models. This empowers decision-makers in the financial sector to respond promptly to threats and minimize losses. Additionally, AI can automatically generate recommendations for optimizing resource allocation for post-disaster recovery and aid. Integration of AI into insurance systems enables personalized insurance policies that better match the specific risks of individuals or organizations. AI also enhances claims processes, expediting damage assessment and claims handling. However, challenges such as data access, privacy, and ethical considerations also need to be carefully addressed to ensure the effective and responsible application of AI in reducing financial losses caused by disasters. Ultimately, the integration of AI into risk management opens the path to a more efficient and resilient financial sector in facing the challenges of disasters.